(untitled) (Journal of actual problems of jurisprudence, 2020)
Abstract. In this article on the basis of statistical information within recent years the structure, condition and general dynamics of corruption offenses in Kazakhstan and its neighboring countries (Russian Federation and Kyrgyz Republic) are studied. The total number of registered criminal offenses in Kazakhstan and Russian Federation has decreased (from 361689 registered in 2016 to 292286 registered in 2018 in Kazakhstan and from 2 160 063 registered in 2016 to 1 991 532 registered in 2018 in Russian Federation) while in Kyrgyz Republic it on the contrary has increased (from 27481 registered in 2016 году to 29718 registered in 2018). However the share of corruption crimes in Kazakhstan and Russian Federation remains at approximately the same level while in Kyrgyz Republic it is decreasing (from 4,1% 22016 to 3,3% in 2018). According to the Committee on Legal Statistics and Special Accounts of the State Office of Public Prosecutor of the Republic of Kazakhstan, the corruption crime structure is mostly consist of such crimes as receiving and giving a bribe, forgery committed by official, abuse of authority, fraud, misappropriation or embezzlement of entrusted property. In neighboring countries (Russian Federation and Kyrgyz Republic), the situation doesn’t differ dramatically – bribery dominates in both states. Almost all surveyed countries are at approximately the same level (28-31) in terms of corruption perception index. However, at the end of 2018 Kazakhstan scored 31 points and took 124th place, ahead of the Russian Federation and took leading position among the countries of Central Asia. This means that despite the fact that the share of corruption offenses in the republic remains at the same level, certain positive trends have also appeared. In other words, the complex of measures taking by our government to counteract corruption brings the desired results. Key words: corruption, offenses, crime, bribe, state.